Horses in the thoroughbred breeding program (1940)
Four of the six thoroughbred mares donated to Cal Poly by the California Breeders Association. The horses' names (L-R): Vibrant (by Light Brigade--Lady Madcap, in foal to Soon Over, donated by Charles E. Perkins), Bon Eva (by Bon Homme--Evalyn, in foal to Naishapur, donated by Bing Crosby), Shasta Red (by Bistouri--Redita V, in foal to Sarada, donated by Charles E. Cooper), and Lone Star Miss (by Gnome--Donno Mamona, in foal to High Step, donated by Walter H. Hoffman, Jr).